In Situ Gelling Ophthalmic Drug Delivery System For Glaucoma - APARNA V. BHALERAO; SITANSHU S. SINGH; APARNA V. BHALERAO (International Journal of Pharma and Bio Sciences, 2011)
Elevated intraocular pressure (IOP) is accepted as the single most important risk factor for glaucoma. The present work describes the formulation and evaluation of an ophthalmic delivery system of an antiglaucoma agent, dorzolamide hydrochloride, based on the concept of ion-activated in situ gelation. Sodium alginate was used as the gelling agent in combination with HPC (Hydroxy Propyl Cellulose) that acted as a viscosity-enhancing agent. In vitro release studies indicated that the alginate/HPC solution retained the drug better than the alginate or HPC solutions alone. The formulations were therapeutically efficacious, stable and provided sustained release of the drug over a period 10 hrs. These results demonstrate that the developed system is an alternative to conventional ophthalmic drops in view of patient compliance, industrially oriented and economical.